2017
DOI: 10.1161/atvbaha.117.309575
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Inhibition by MCC950 Reduces Atherosclerotic Lesion Development in Apolipoprotein E–Deficient Mice—Brief Report

Abstract: These findings show that specific inhibition of the NLRP3 inflammasome using MCC950 can be a promising therapeutic approach to inhibit atherosclerotic lesion development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(179 citation statements)
references
References 23 publications
2
170
0
Order By: Relevance
“…IL-1␤ plays a pivotal role in signaling of other inflammatory cytokines. Emerging evidence suggests a key role for the inflammasome in atherosclerotic disease progression (73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83) and in HIV-1 disease (47,(84)(85)(86)(87)(88)(89). Inflammasome activation requires two signals, one for priming (i.e., TLR signaling which results in transcriptional regulation) and then one for activation of inflammasome complex assembly.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1␤ plays a pivotal role in signaling of other inflammatory cytokines. Emerging evidence suggests a key role for the inflammasome in atherosclerotic disease progression (73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83) and in HIV-1 disease (47,(84)(85)(86)(87)(88)(89). Inflammasome activation requires two signals, one for priming (i.e., TLR signaling which results in transcriptional regulation) and then one for activation of inflammasome complex assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive NLRP3 inflammasome activity is responsible for chronic inflammation that drives pathological processes in multiple diseases, including atherosclerosis, Alzheimer's disease, fulminant hepatitis, and diabetes (2,3,20,22). In fact, many of these disease processes are significantly attenuated in mice that lack NLRP3 inflammasome functionality (22)(23)(24). Thus, the NLRP3 inflammasome has emerged as a valid pharmacological target for the treatment of a range of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, NLRP3‐deficient mice have been reported to exhibit significant protection from high fat diet‐induced metabolic syndrome, characterized by reduced sterile inflammation (i.e., a decrease in the frequency of effector T cell infiltrate in visceral adipose tissue), reduced adipocyte hypertrophy and liver steatosis, and preservation of pancreatic β‐cell mass that results in improved insulin sensitivity and glucose tolerance . A number of studies have now largely confirmed this pathogenic role for NLRP3 and ASC in obesity‐related disorders, such as insulin resistance and Type 2 diabetes, nonalcoholic steatohepatitis (NASH) and cardiovascular disease (e.g., atherosclerosis) …”
Section: Nlrp3 In Health and Diseasementioning
confidence: 97%